2012
DOI: 10.1148/radiol.12112672
|View full text |Cite
|
Sign up to set email alerts
|

Nonmalignant Breast Lesions: ADCs of Benign and High-Risk Subtypes Assessed as False-Positive at Dynamic Enhanced MR Imaging

Abstract: Purpose:To evaluate the diffusion-weighted (DW) imaging characteristics of nonmalignant lesion subtypes assessed as false-positive findings at conventional breast magnetic resonance (MR) imaging. Materials and Methods:This HIPAA-compliant retrospective study had institutional review board approval, and the need for informed patient consent was waived. Lesions assessed as Breast Imaging Reporting and Data System category 4 or 5 at clinical dynamic contrast material-enhanced MR imaging that subsequently proved n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 59 publications
3
49
1
1
Order By: Relevance
“…Use of DWI together with T2-weighted images created a good unenhanced imaging alternative to DCE-MRI in lesion detection and characterization. This method was previously used in some experimental clinical and reader studies and found to be useful for the diagnosis of breast cancer (24)(25)(26)(27). Lastly, Trimboli et al (28) reported 78% sensitivity and 87% specificity for breast cancer detection with unenhanced MRI of 67 women.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Use of DWI together with T2-weighted images created a good unenhanced imaging alternative to DCE-MRI in lesion detection and characterization. This method was previously used in some experimental clinical and reader studies and found to be useful for the diagnosis of breast cancer (24)(25)(26)(27). Lastly, Trimboli et al (28) reported 78% sensitivity and 87% specificity for breast cancer detection with unenhanced MRI of 67 women.…”
Section: Discussionmentioning
confidence: 98%
“…High T2 signal can help diagnose active fibroadenomas most of the time. Fibroadenoma is most common diagnosis in low-risk breast masses and most prevalent lesion type that shows high ADC values (27). However, an uncommon malignancy of elderly women (mucinous cancers) also shows bright signal on T2-weighted images and can cause misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with DCE, DWI scans have significantly elevated the specificity and accuracy in the diagnosis of breast cancer compared with DCE-MRI alone. 4,6 Based on DWI, diffusion tensor imaging (DTI) could detect more information about the microstructure. 7 DTI could provide not only the average apparent diffusion coefficient (ADC), but also three-dimensional anisotropy diffusion parameters such as fractional anisotropy (FA).…”
Section: Introductionmentioning
confidence: 99%
“…The cutoff value of ADC to differentiate between benign and malignant lesions as per this study was 1.81x10 -3 mm 2 /s. Sana Parsian et al, (6) Table 7.3: Table comparing validity paramaters of present and previous study for a sensitivity of 100% F Kelcz et al, (7) in a study evaluating cases of post lumpectomy irradiated breast have found a mean ADC value of 1.89 ( range 1.43-2.20). These findings are well correlating with our studythere were 6 cases, all of which showed unrestricted diffusion.…”
Section: Diffusion Weighted Imaging and Adc Valuementioning
confidence: 60%